Heterogeneity of Phospholipid Composition in the Bacterial Membrane - Tucker, Anne N. (1970)
Heterogeneity in the distribution or binding of the membrane phospholipids was demonstrated in the membrane fragments released from Haemophilus parainfluenzae by treatment with ethylenediaminetetraacetic acid (EDTA)-tris(hydroxymethyl)-aminomethane (Tris). The membrane fragments released early in the EDTA-Tris treatment contained two- to fivefold higher proportions of cardiolipin and phosphatidylglycerol and less phosphatidylethanolamine as well as phospholipids with threefold lower specific activity of the phospholipid phosphate after a short pulse of (32)P than were found in the residue. Heterogeneity was best demonstrated with shorter EDTA-Tris treatments and shorter periods of growth with (32)P. EDTA-Tris treatment appeared to progressively strip phospholipids from the cells that were synthesized at progressively later times.